A Molecular Popeye: Li+@C60 and its Complexes with [n]Cycloparaphenylenes - Freiberger, Markus; Solymosi, Iris; Freiberger, Eva Marie; Hirsch, Andreas; Perez-Ojeda Rodriguez, Maria Eugenia; Drewello, Thomas (Nanoscale, 2023)
In this work, we compare for the first time the stability of [n]cycloparaphenylene ([n]CPP)-based host–guest complexes with Li+@C60 and C60 in the gas and the solution phase. Our gas-phase experiments reveal a significant increase in stability for the complexes featuring [9–12]CPP with Li+@C60. This increased interaction strength is also observed in solution. Isothermal titration calorimetry shows for the formation of [10]CPP⊃Li+@C60 a two orders of magnitude larger association constant than that for the C60 analog. Additionally, an increased binding entropy is observed. This study contributes to a better understanding of host–guest complexes between [n]CPPs and endohedral metallofullerenes at a molecular level, which is the prerequisite for future applications.

Bromination of 2D materials - Freiberger, Eva Marie; Steffen, Julien; Waleska-Wellnhofer, Natalie; Hemauer, Felix; Schwaab, Valentin; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Nanotechnology, 2024)
The adsorption, reaction and thermal stability of bromine on Rh(111)-supported hexagonal boron nitride (h-BN) and graphene were investigated. Synchrotron radiation-based high-resolution x-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS allowed us to follow the adsorption process and the thermal evolution in situ on the molecular scale. On h-BN/Rh(111), bromine adsorbs exclusively in the pores of the nanomesh while we observe no such selectivity for graphene/Rh(111). Upon heating, bromine undergoes an on-surface reaction on h-BN to form polybromides (170-240 K), which subsequently decompose to bromide (240-640 K). The high thermal stability of Br/h-BN/Rh(111) suggests strong/covalent bonding. Bromine on graphene/Rh(111), on the other hand, reveals no distinct reactivity except for intercalation of small amounts of bromine underneath the 2D layer at high temperatures. In both cases, adsorption is reversible upon heating. Our experiments are supported by a comprehensive theoretical study. DFT calculations were used to describe the nature of the h-BN nanomesh and the graphene moiré in detail and to study the adsorption energetics and substrate interaction of bromine. In addition, the adsorption of bromine on h-BN/Rh(111) was simulated by molecular dynamics using a machine-learning force field.
CRIS-Team Scopus Importer:2024-02-09
Keywords: bromine; functionalization; graphene; hexagonal boron nitride; machine-learning force field; molecular dynamics; x-ray photoelectron spectroscopy

Bromine Adsorption and Thermal Stability on Rh(111): A Combined XPS, LEED and DFT Study - Freiberger, Eva Marie; Steffen, Julien; Waleska-Wellnhofer, Natalie; Harrer, Anton; Hemauer, Felix; Schwaab, Valentin; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (ChemPhysChem, 2023)
This study addresses a fundamental question in surface science: the adsorption of halogens on metal surfaces. Using synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (XPS), temperature-programmed XPS, low-energy electron diffraction (LEED) and density functional theory (DFT) calculations, we investigated the adsorption and thermal stability of bromine on Rh(111) in detail. The adsorption of elemental bromine on Rh(111) at 170 K was followed in situ by XPS in the Br 3d region, revealing two individual, coverage-dependent species, which we assign to fcc hollow- and bridge-bound atomic bromine. In addition, we find a significant shift in binding energy upon increasing coverage due to adsorbate-adsorbate interactions. Subsequent heating shows a high thermal stability of bromine on Rh(111) up to above 1000 K, indicating strong covalent bonding. To complement the XPS data, LEED was used to study the long-range order of bromine on Rh(111): we observe a (√3×√3)R30° structure for low coverages (≤0.33 ML) and a star-shaped compression structure for higher coverages (0.33–0.43 ML). Combining LEED and DFT calculations, we were able to visualize bromine adsorption on Rh(111) in real space for varying coverages.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adsorption sites; halogens on metals; high-resolution X-ray photoelectron spectroscopy; LEED; synchrotron radiation

Engineering large nanoporous networks with size and shape selected by appropriate precursors - Ceccatto, Alisson; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Jaekel, Simon; Mowbray, Duncan John; Papp, Christian; Steinrück, Hans-Peter; de Siervo, Abner (Carbon, 2024)
Large domains of two-dimensional supramolecular porous nanostructures are interesting for various applications from electronics to biology. Here, we investigate the formation of Cu-coordinated networks on Cu(111) using scanning tunneling microscopy and density functional theory (DFT). We consider two molecules with three pyridyl end groups connected to a central benzene ring by either one or two phenyl groups, namely 1,3,5-tris[4-(pyridin)phenyl]benzene (TPyPB) and 1,3,5-tris[4-(pyridin)-[1,1’-biphenyl]benzene (TPyPPB), respectively. Upon deposition of TPyPB at room temperature, a honeycomb nanostructure forms, which is stabilized by Cu adatoms, as previously seen. Upon deposition at 400 K, the growth dynamics change, and molecules become trapped in the hexagonal pores. In contrast, deposition of TPyPPB at room temperature leads to vitreous structures, which rearrange at 400 K forming a low-defect and extended ordered honeycomb phase, which is also stabilized only in the presence of Cu adatoms. The DFT calculations for both honeycomb phases show an impressive agreement with the experimental results, considering the size of such structures. After annealing at 420 K, a complex flower-like structure composed of a mix of two- and three-fold coordinated Cu centers emerges. Further annealing to above 420 K leads to another new phase composed of a high molecular density motif, the so-called diamond phase.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Cu(111); Metal coordination; Nanoporous organic network; On-surface synthesis; Scanning tunneling microscopy; TPyPB; TPyPPB

Engineering two-dimensional supramolecular self-assembly: The role of Cl atoms - Ceccatto, Alisson; Campi, Gustavo Ramon; Diaz, Vanessa Carreño; da Costa Ferreira, Eidsa Brenda; Waleska-Wellnhofer, Natalie; Freiberger, Eva Marie; Jaekel, Simon; Papp, Christian; Steinrück, Hans-Peter; Mowbray, Duncan John; de Siervo, Abner (FlatChem, 2025)
On-surface synthesis is a powerful tool for engineering two-dimensional (2D) organic nanostructures by controlling intermolecular interactions between the building blocks. Herein, we explore the role of Cl adatoms in the synthesis and characterization of self-assembled 1,3,5-tris[4-(pyridin)-[1,1’-biphenyl]benzene (TPyPPB) networks on Ag(111), by combining scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT). In the absence of Cl, upon deposition at room temperature (RT), TPyPPB molecules form a highly ordered porous supramolecular network with triangular packing, stabilized by hydrogen bonds (N⋯H). In the presence of Cl adatoms, sublimated onto the surface using dichloro-(1,10-phenanthrolin)-platin(II) (Cl2PhPt) a second molecular precursor, we observe a so-called mixed phase or inverted packing, depending on the applied growth procedure. The mixed phase is characterized by a non-periodic structure stabilized by intermolecular interactions between TPyPPB, Cl2PhPt, and Cl. In contrast, when only Cl adatoms and TPyPPB are present on the Ag(111) surface, a non-porous supramolecular arrangement is obtained, stabilized by C–H⋯Cl hydrogen bonds.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Chlorine-mediated network; Nanoporous organic network; On-surface synthesis; Scanning tunneling microscopy; TPyPPB

h-BN in the making: The surface chemistry of borazine on Rh(111) - Freiberger, Eva Marie; Düll, Fabian; Bachmann, Phiona; Steinhauer, Johann; Williams, Federico J.; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2024)
Borazine is a well-established precursor molecule for the growth of hexagonal boron nitride (h-BN) via chemical vapor deposition on metal substrates. To understand the formation of the h-BN/Rh(111) moiré from borazine on a molecular level, we investigated the low-temperature adsorption and thermally induced on-surface reaction of borazine on Rh(111) in situ using synchrotron radiation-based high-resolution x-ray photoelectron spectroscopy (XPS), temperature-programmed XPS, and near-edge x-ray absorption fine structure measurements. We find that borazine adsorbs mainly as an intact molecule and have identified a flat-lying adsorption geometry. Borazine multilayers are observed to desorb below 200 K. Starting at about 300 K, dehydrogenation of the remaining borazine and borazine fragments takes place, and disordered boron nitride starts to grow. Above 600 K, the formation of the h-BN sets in. Finally, at 1100 K, the conversion to h-BN is complete. The h-BN formed by deposition and post-annealing was compared to the h-BN grown by an established procedure, proving the successful preparation of the desired two-dimensional material.
CRIS-Team Scopus Importer:2024-05-10

In Situ Investigation of the Cu/CH3NH3PbI3 Interface in Perovskite Device - Ding, Honghe; Yan, Kangrong; Li, Bairu; Hu, Wanpei; Jia, Lingbo; Zareen, Shah; Freiberger, Marie; Huang, Jianmin; Hu, Jun; Xu, Qian; Li, Yu; Yang, Shangfeng; et al. (Advanced Materials Interfaces, 2021)
In this study, the electronic properties and chemical stability of the Cu/CH3NH3PbI3 interface are investigated in situ by a combination of X-ray photoelectron spectroscopy and synchrotron radiation photoemission spectroscopy (SRPES). The morphology of Cu deposited perovskite surface is monitored by scanning electron microscopy. The results show that the Cu/CH3NH3PbI3 interface is very stable and no chemical reaction between Cu and the perovskite takes place. Moreover, a 0.45 eV interface dipole and a 0.15 eV upward band bending are obtained at the Cu/CH3NH3PbI3 interface. Based on these fundamental findings, a prototype of Cu/CH3NH3PbI3/NiOx/indium tin oxide solar cell device is constructed to check the power conversion efficiency (PCE) and device stability. Although no electron transport material is used in this device, it still exhibits decent performance. The PCE of the device reaches up to 9.99% and remains almost unchanged over a long-time (49 d) storage in a N2-filled glovebox. Through this study it is demonstrated that fundamental understanding of the interfacial structure of a perovskite solar cell is essential in pursuit of rational design of superior perovskite solar cells, and moreover, Cu is a promising electrode candidate for perovskite solar cells.
CRIS-Team Scopus Importer:2021-06-04
Keywords: interfacial structure; long-term storage stability; perovskite solar cells; photoemission spectroscopy; power conversion efficiencies

Liquid Organic Hydrogen Carriers: Model Catalytic Studies on the Thermal Dehydrogenation of 1-Cyclohexylethanol on Pt(111) - Schwaab, Valentin; Hemauer, Felix; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2023)
The molecule pair of 1-cyclohexylethanol and acetophenone represents an interesting system for a chemical hydrogen storage cycle as it combines two different classes of so-called liquid organic hydrogen carriers (LOHCs), namely hydrogenated, formerly aromatic cyclic hydrocarbons and alcohols, i.e., hydrogenated carbonyls. In particular, the latter have recently attracted much attention due to their favorable dehydrogenation temperatures and the possibility to convert them directly into electricity in specially designed direct-LOHC fuel cells. Herein, we investigate the temperature-triggered dehydrogenation reaction of 1-cyclohexylethanol to acetophenone on a Pt(111) model catalyst using synchrotron-based temperature-programed X-ray photoelectron spectroscopy. To obtain a complete picture of the reaction mechanism, we consider not only the individual surface reactions of 1-cyclohexylethanol and acetophenone but also those of two potential dehydrogenation intermediates, namely, the partially dehydrogenated 1-cyclohexylethanone and 1-phenylethanol. We find a stepwise dehydrogenation of 1-cyclohexylethanol: the first step around ∼210 K at the alcohol moiety yields the ketone 1-cyclohexylethanone. The second step above ∼260 K at the cyclohexyl group is accompanied by the loss of an H-atom at the molecule’s methyl group and leads to the formation of an acetophenone-like phenyl-C(O)-CH2 species at ∼340 K. The same species are also identified in the surface reactions of acetophenone, 1-phenylethanol, and 1-cyclohexylethanone in this temperature range. Overall, the system shows good thermal robustness: a complete dehydrogenation of the hydrogen-rich carrier occurs without damage to the carbon framework.
CRIS-Team Scopus Importer:2023-07-07

Model Catalytic Studies of Liquid Organic Hydrogen Carriers: Indole/Indoline/Octahydroindole on Ni(111) - Steinhauer, Johann; Bachmann, Philipp; Freiberger, Marie; Bauer, Udo; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
N-heterocycles belong to the class of so-called liquid organic hydrogen carriers (LOHCs), which have been identified as suitable materials for chemical hydrogen storage due to favorable hydrogen storage capacity and reaction kinetics. In this contribution, we focus on the dehydrogenation reaction of hydrogen-rich octahydroindole, its dehydrogenation intermediate indoline, and hydrogen-lean indole. Octahydroindole has a hydrogen storage capacity of 6.4 wt %, and indoline has 1.7 wt %. We investigated the mechanism of the temperature-induced dehydrogenation of the three compounds after adsorption on Ni(111) at low temperatures. Nickel is attractive as an effective and low-priced dehydrogenation catalyst, which potentially could replace more expensive Pt and Pd in industrial applications. We compare the obtained results with our previous work on Pt(111) for the same LOHC system and for N-ethylcarbazole/H-12-N-ethylcarbazole. A comprehensive understanding of the reaction mechanism was obtained by combining high-resolution X-ray photoelectron spectroscopy with temperature-programmed desorption lab experiments. For all three compounds, we find dehydrogenation at the nitrogen atom above 270 K (indole, >= 130 K; indoline, >240 K; octahydroindole, >270 K). For indoline and octahydroindole, we observe simultaneous dehydrogenation at the carbon atoms, resulting in an indolide surface species. For octahydroindole, small amounts of side products and decomposition products are observed throughout the reaction pathway. Above 380 K, the indolide species decomposes into fragments for all three compounds.
CRIS-Team WoS Importer:2020-11-27

Nano-SMSI on Bimetallic FePt Clusters - Waleska-Wellnhofer, Natalie; Freiberger, Marie; Hemauer, Felix; Schwaab, Valentin; Papp, Christian (Journal of Physical Chemistry C, 2023)
Nano-strong metal-support interaction is observed in this work for bimetallic FePt nanoclusters on graphene/Rh(111). FePt clusters were prepared by successively depositing 1.27 ML Fe and 0.14 ML Pt on the graphene/Rh(111) substrate. Oxidation of Fe was achieved by CO dissociation, while CO was simultaneously used as a probe molecule to gather information about the clusters’ structure. After UHV annealing to 550 K, encapsulation of Pt with an Fe oxide layer and a strong decrease of the chemisorption capacity of the clusters was found. Further increase of the temperature to 900 K leads to the decomposition of the Fe oxide layer and the intercalation of Fe. Besides, the formation of an FePt alloy was observed at elevated temperature.
CRIS-Team Scopus Importer:2023-11-03

Surface Studies on the Energy Release of the MOST System 2-Carbethoxy-3-Phenyl-Norbornadiene/Quadricyclane (PENBD/PEQC) on Pt(111) and Ni(111) - Hemauer, Felix; Schwaab, Valentin; Freiberger, Eva Marie; Waleska, Natalie; Leng, Andreas; Weiß, Cornelius; Steinhauer, Johann; Düll, Fabian; Bachmann, Philipp; Hirsch, Andreas; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2023)
Novel energy-storage solutions are necessary for the transition from fossil to renewable energy sources. Auspicious candidates are so-called molecular solar thermal (MOST) systems. In our study, we investigate the surface chemistry of a derivatized norbornadiene/quadricyclane molecule pair. By using suitable push–pull substituents, a bathochromic shift of the absorption onset is achieved, allowing a greater overlap with the solar spectrum. Specifically, the adsorption and thermally induced reactions of 2-carbethoxy-3-phenyl-norbornadiene/quadricyclane are assessed on Pt(111) and Ni(111) as model catalyst surfaces by synchrotron radiation-based X-ray photoelectron spectroscopy (XPS). Comparison of the respective XP spectra enables the distinction of the energy-rich molecule from its energy-lean counterpart and allows qualitative information on the adsorption motifs to be derived. Monitoring the quantitative cycloreversion between 140 and 230 K spectroscopically demonstrates the release of the stored energy to be successfully triggered on Pt(111). Heating to above 300 K leads to fragmentation of the molecular framework. On Ni(111), no conversion of the energy-rich compound takes place. The individual decomposition pathways of the two isomers begin at 160 and 180 K, respectively. Pronounced desorption of almost the entire surface coverage only occurs for the energy-lean molecule on Ni(111) above 280 K; this suggests weakly bound species. The correlation between adsorption motif and desorption behavior is important for applications of MOST systems in heterogeneously catalyzed processes.
CRIS-Team Scopus Importer:2023-03-31
Keywords: catalysis; energy storage; MOST system; photoelectron spectroscopy; surface reactions